Regeneration of Cocoa Zygotic Embryo Using Kinetin in B5 Media - Sholeh Avivi (Jurnal ILMU DASAR, 2011)
The objective of this research was intended to identify the influence of kinetin application on zygotic embryo regeneration of several cocoa plants and examine the most appropriate kinetin concentration for regeneration of several cocoa clones. This research was conducted at Laboratory of Plant Tissue Culture, Agronomy Department, Faculty of Agriculture,Jember University. The research was designed by Completely Randomized Factorial Design within four replications. The first factor was 4 cocoa clones which consisted of DR 1, DR 2, ICS13 and ICS60.The second factor was 5 methods of zygotic embryo regeneration. Result showed that the best response of cocoa clone to kinetin concentration of all examined parameters was shown by DR 1 clone. Morever, on initiation stage, the most appropriate kinetin concentration for regeneration of several cocoa clones was 2 ppm.